Why do people use fitness tracking devices in Thailand? An integrated model approach - Michael Naglis (2020)
© 2019 Elsevier Ltd A three-pronged approach was used in this study consisting of a very comprehensive review of the literature, interview with experts, and a field survey to propose a model of user acceptance of fitness tracking devices in Thailand. The proposed model is an integrated model consisting of the technology acceptance model, flow theory, and innovation diffusion theory. A survey consisting of 452 fitness tracking users was undertaken in the Greater Bangkok region. Examinations of both convergent and discriminant validities were conducted. The results of the structural equation modeling illustrate that perceived ease of use, perceived usefulness, behavioral intention, perceived enjoyment, result demonstrability, visibility, and trialability posit a statistically positive relationship with fitness tracking device acceptance. Contrary to other technology acceptance studies, perceived control, concentration, and compatibility did not posit a positive relationship with fitness tracking device acceptance. Discussions of the findings and conclusions along with implications and limitations are presented in this study. This study is also one of the first few to investigate the acceptance of fitness tracking devices in the context of a developing country, in this case Thailand.